Effectiveness of Bit (Beta vulgaris L.) Fruit Pressed Water as A Natural Color on Examination of Fests Confirmed with Helminthiasis - Wahyuni, Tri; Aisyah, Riandini; Bestari, Rochmadina; Kurniati, Yuni Prestyo (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: Helminthiasis is a significant public health issue, particularly in tropical and subtropical regions. The conventional staining method using 2% eosin, while effective, poses environmental and health concerns due to its carcinogenic properties and poor biodegradability. An alternative, natural, and environmentally friendly dye is necessary. Beetroot (Beta vulgaris L.), rich in betalain pigments, offers a potential solution. Aim: This study aims to evaluate the effectiveness of beet juice as a natural dye for microscopic examination of helminthiasis and assess its performance when combined with 9% citric acid. Methodology: A true experimental design with a posttest-only control group approach was employed. Beet juice concentrations of 70%, 80%, 90%, and 100% were prepared, both with and without 9% citric acid. Stool samples confirmed with helminthiasis were stained using these solutions and examined microscopically. The criteria assessed were effectiveness of coloration, visualization of parasite structure, and quality of staining results. Data were analyzed using the Kruskal-Wallis test. Results: Beet juice at all concentrations showed comparable effectiveness to 2% eosin across all parameters. Adding 9% citric acid enhanced the stability and longevity of the beet juice, maintaining color quality for up to 21 days, compared to 8 days without citric acid. Statistical analysis showed no significant differences between the staining results of beet juice and eosin (p > 0.05). Discussion: beetroot (Beta vulgaris L.) contains betasiani pigments and flavonoids which are antioxidants with an acidic pH that can color the protein layer of worm eggs which are alkaline in nature. Conclusion: Beet juice, particularly when combined with 9% citric acid, is a viable, natural alternative to 2% eosin for helminthiasis staining. It offers a safer and environmentally friendly option with comparable effectiveness and longer durability.